Behavioral Stimulus for Using Bank Mestika Mobile Banking Services: UTAUT2 Model Perspective - Fenny Krisna Marpaung; Reni Shinta Dewi; Ernest Grace; Acai Sudirman; Maria Sugiat (Manunggal Halim Jaya, 2021)
The existence of mobile banking services is currently experiencing rapid growth. Adopting such a large number of users makes mobile banking services one of the main needs to meet the needs of conducting financial transactions. Therefore, there is a need for additional information for mobile banking service developers on the dominant factors influencing user behavioral intentions. This research is present as a forum to provide an overview of the user's perspective on Mestika bank's mobile banking service. This research aims to find out what factors play an important role in behavioral intention to use Mestika bank's mobile banking services based on the UTAUT2 concept. The research instrument used a questionnaire distributed online to 240 respondents in Medan City and Pematangsiantar City, Indonesia. Next, the researcher tested the hypothesis using Structural Equation Modeling (SEM) based on a variant called Partial Least Square (PLS) and the SmartPLS version 3.0 application as a tool to analyze it. This research concludes that effort expectancy has the most significant influence and plays a very important role in shaping the behavioral intention of using Mestika bank's mobile banking. Then performance expectancy and social influence hedonic motivation also significantly influence behavioral intentions to use Mestika bank's mobile banking. Furthermore, the results of this study also conclude that facilitating conditions and habit have no significant effect on behavioral intentions to use Mestika bank's mobile banking.